2017
DOI: 10.1088/1741-4326/aa6aba
|View full text |Cite
|
Sign up to set email alerts
|

Losses of runaway electrons in MHD-active plasmas of the COMPASS tokamak

Abstract: Significant role of magnetic perturbations in mitigation and losses of Runaway Electrons (REs) was documented in dedicated experimental studies of RE at the COMPASS tokamak. RE in COMPASS are produced both in low density quiescent discharges and in disruptions triggered by massive gas injection (MGI). The role of the RE seed produced in the beginning of the discharge on the subsequent RE population proved significant. Modulation of the RE losses by MHD instabilities was observed at several characteristic frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 17 publications
(24 reference statements)
4
36
0
Order By: Relevance
“…(center) TCV controlled ramp-down with (#61503, also with current oscillations) and without (#61501) the REB-C that is used to obtain (right) a large RE beam vertical displacement of about 11 cm, shot #61096. 16 Similar results where electrical field oscillations have induced RE losses have been discussed in [21] and [4].…”
Section: Position Controlsupporting
confidence: 57%
“…(center) TCV controlled ramp-down with (#61503, also with current oscillations) and without (#61501) the REB-C that is used to obtain (right) a large RE beam vertical displacement of about 11 cm, shot #61096. 16 Similar results where electrical field oscillations have induced RE losses have been discussed in [21] and [4].…”
Section: Position Controlsupporting
confidence: 57%
“…The first spectrogram shows magnetic activity of the plasma which affects the RE radiation, which can be seen in the second spectrogram. Similar correlations have been previously seen at the COMPASS tokamak between the HXR intensity and magnetic activity of the plasma [19]. Periodic oscillations, such as in shot 21213, have been discovered in almost all SXR signals, including shots from the 11th RE campaign.…”
Section: Jinst 17 P02030supporting
confidence: 81%
“…That dependence was observed, e.g., during experimental campaigns dedicated to studies of the RE emission at the COMPASS tokamak. It was observed that RE in the COMPASS can be produced due to two circumstances: very quiescent discharges performed at a low plasma density, or in the case when the plasma current disruption is initiated by the massive gas injection (MGI) [4]. The MHD instabilities are able to induce a modulation of the RE losses, as it was observed in the COMPASS and other tokamaks, e.g.…”
Section: Introductionmentioning
confidence: 93%
“…That puffing was usually performed during the current ramp-up phase, and it initiated a disruption. It made possible to perform experiments on the RE control and mitigation [4,12]. The measurements carried out by means of the Cherenkov probe showed that the first fast-electron peak appears usually at the current ramp-up phase, even before the hard X-rays (HXR) pulse.…”
Section: Measurements Of Fast Electronsmentioning
confidence: 99%